(untitled) (Innovaciones Educativas, 2019)
This paper proposes an analysis of some challenges in today`s education from human rights framework: the consideration of the human rights and human duties, the educational inclusive, the quantity of school years completed, the influence of the technology on student`s characteristics, and the incertitude of the humanities future, all of these elements are considered from the Humanism. Thereby, the goal of this paper is the treat of some situations that the education`s professionals need to know, also the students, in special because of the crisis of some actually learning methodologies what trying to resist the changes in a globalizing world that goes toward the development of skills as change capacity, the innovation, the creativity and the change adaptation.